Sayed`s Theory on Unification of Electromagnetism and Gravity Forces: Innovative Correlation of Electrodynamics and Gravity with Inevitable Violation of E=mc - El-Mongy, Sayed (JOURNAL OF ADVANCES IN PHYSICS, 2025)
The unified universe is a function in the only Great Creator, Allah. The unification of the weak nuclear force and electromagnetism was achieved in 1979 by Noble laureates. This article is a theory and outstanding approach for unification of electromagnetism and gravity forces. The Sayed`s electromagnetic-gravity force (SEMGF) equations were derived and generated by fusion of Newton, Einstein, Planck, Maxwell equations and Coulomb law. The violation of E=mc2 is remarkably concluded. The unified equations lead to introduce the effect of electromagnetic gravity force on the measured and calculated speed of light. The acceleration, wavelength, gravitational constant, Planck constant, and speed of light were also integrated to develop Maxwell`s equations. The magnetic to electric field ratio was postulated to be π. To verify some universal constants taking into consideration the electromagnetic gravity force, speed of light was served to be violated: ~ 6 x1016 m/s. The Planck force and acceleration were found to be in concordance with the calculated by SEMGF; 1.21029x1044 N and 5.6077x1051 m/s2 respectively. The calculated gravitational constant (G) and electrostatic charge (e) values are; 6.67 x 10-11 Nm2/kg2 and 1.602x10-19 C. Some values show differences that could be due to mutual and overlapping effect of the gravity and electromagnetism forces. It is a deep step for unification of gravity and electromagnetism.